Elevated Preoperative Neutrophil-Lymphocyte Ratio Is Associated with Poor Prognosis in Hepatocellular Carcinoma Patients Treated with Liver Transplantation: A Meta-Analysis - Xiao-Dong Sun; Xiao-Ju Shi; Yu-Guo Chen; Chuan-Lei Wang; Qiang Ma; Guo-Yue Lv (Gastroenterology Research and Practice)
This study aims to investigate the prognostic value of neutrophil to lymphocyte ratio (NLR) in hepatocellular carcinoma (HCC) patients treated with liver transplantation (LT) through meta-analysis. Relevant articles were sought in PubMed, Embase, and Wangfang databases up to July 2015. A total of 1687 patients from 10 studies were included in this meta-analysis. Meta-analysis results showed that elevated NLR was significantly associated with poorer overall survival (OS) (HR = 2.71, 95% CI: 1.91–3.83) and poorer disease-free survival (DFS) (HR = 3.61, 95% CI: 2.23–5.84) in HCC patients treated with LT. Moreover, subgroup analysis showed the significant association between elevated preoperative NLR and poor prognosis was not altered by cutoff values of NLR or types of LT. Therefore, elevated preoperative NLR is associated with poor prognosis in HCC patients treated with LT. Preoperative NLR should be used to predict the prognosis of HCC after LT in our clinical work.